PEMBINAAN PRAKTEK SHALAT DAN WUDHU PADA PEMUDA DAN REMAJA DI PERUMAHAN KOTA TANJUNGPINANG - Efendi, Zulfan; Artilita, Sindy; Mizuardi, Mizuardi; Sumayah, Sumayah (As-Sidanah : Jurnal Pengabdian Masyarakat, 2023)
The internalization of religious teachings which is considered effective for teenagers and young people is through the implementation of religious guidance, which starts from the family, school and community environment. The main parameter is how teenagers and youth are able to maintain, maintain and carry out the spiritual worship that has been required of them, so that it becomes an identity and characteristic for their religion. The target of coaching carried out in this service is an effort to increase awareness and transfer knowledge in order to add insight to teenagers and youth who are at the Mizan Mosque Vallian Housing Permai Pinang Kencana, Tanjung Pinang City. The method used as an analytical tool in this study is the Participatory Action (PAR) method, which is a participatory research method among members of a community whose goal is to encourage transformative action to liberate society from the shackles of ideology and power relations (change) in living conditions for the better. From this study it was concluded that after participating in community service, adolescents and youths were able to practice and apply the teachings of their worship in everyday life, especially in carrying out spiritual worship, namely performing ablution and performing prayers.